Variabilidade ambiental e a distribuição de abundância de copépodes (Crustacea: Copepoda) de planícies de inundação neotropicais. - Amaral, Diogo Castanho (2014)
The environmental variables are important in the functioning and dynamics of freshwater ecosystems, since changes in physical and chemical conditions of these environments contribute to alterations in the ecological functioning. This research was conducted in four neotropical flood plains: Amazônica, Araguaia, Pantanal e Paraná. The samples of zooplankton were performed in the subsurface region of limnetic lakes each floodplain, in the years 2011 and 2012 (dry and wet). At the same time the environmental variables were measured and obtained water samples for later laboratory analysis. Our goal was to investigate the effect of environmental variables in the abundance of copepods, and the following hypothesis was tested: HI) the abundance of copepods has a great set with environmental variables, and extremes range of environmental variation, the lower the abundance of these organisms, unimodal effect. Local factors (physical and chemical environmental conditions) determined the abundance of copepods, as well as the environmental gradient showed a close relationship in the spatial and temporal distribution of the species, being possible to observe higher abundance at specific levels of environmental variables (toward the great). Studies that focus on tolerance limits of the species and their relationships with environmental conditions has risen in recent years, as the anthropogenic changes in climate and natural environments has caused significant changes in community structure, facilitating the invasion by non-native species and loss species diversity and the consequent change in ecosystem functioning. However, the hypothesis (HI) was partially supported, as the abundance follows a pattern of rise towards the great, but it was not possible to clearly unimodal effect on abundance for many species.